Modern possibilities of instrumental diagnostics of early stages of avascular osteonecrosis - V. E. Bialik; M. A. Makarov; E. I. Bialik; S. А. Makarov; A. E. Karateev; A. M. Lila; V. A. Nesterenko; A. A. Bialik; D. V. Kapitonov; A. I. Gorelova (Современная ревматология)
Avascular osteonecrosis (AON) is a common condition that can occur at any age, but more often in young and able-bodied people. The disease leads to rapid destruction and collapse of the subchondral bone with subsequent formation of secondary osteoarthritis of the affected joint. The review presents modern methods of instrumental diagnostics of AON. Particular attention is paid to the detection of stage I AON. An approach to early diagnosis of AON is discussed that may change the misconception of viewing bone tissue edema as a sign characteristic only of AON and may improve differential diagnosis of the disease from other conditions and treatment outcomes.